Knowledge transfer and protection in international joint ventures : An integrative review - Kim, Huijeong; Park, Byung Il; Al-Tabbaa, Omar; Khan, Zaheer (Elsevier, 2024)
Cross-border transfer and the protection of knowledge are important for multinational enterprises (MNEs) to develop their network partners’ capabilities while simultaneously safeguarding competitive advantages. However, they can be challenging for MNEs due to cultural and institutional differences between home and host markets. This poses a dilemma for MNEs, which is how to strike a balance between their knowledge transfer (KT) and knowledge protection (KP) strategies. It is notable that, so far, research has primarily investigated these two areas independently, lacking an integrative view. Therefore, in this article, we reviewed 98 academic articles exploring knowledge transfer/protection in MNEs operating under international joint venture (IJV) arrangements and assessed publications from the last two decades (2000–2022). Drawing from institutional theory and the bargaining power perspective, we developed a conceptual framework highlighting the external and internal factors influencing KT and KP. Subsequently, we contextualized these factors within the specific domain of IJVs, drawing on insights gleaned from the studies in our sample. The interplay of these factors, along with their contextual nuances, provides a holistic and in-depth understanding of how knowledge is managed within the complex dynamics of IJVs. In addition, our review contributes to our understanding of knowledge management in MNEs by identifying novel gaps in the literature and suggesting a number of avenues for future research.
Keywords: Knowledge transfer; Knowledge protection; Multinational enterprises; International joint ventures; Integrative review